University Governance: Empirical evidence from Tunisian Public Higher Education Establishments - Khefacha, Islem; Belkacem, Lotfi (Revue Gouvernance / Governance Review, 2010)
This paper investigates the way decisions are taken in Tunisian public higher education establishments. We focus our review on the ubiquitous but not well understood concept of “university governance” Despite the presence of a large body of literature about governance in higher education, the lack of empirical research led us to think that it would be important to “perationalize” the concept of "university governance" in an empirical survey. To do this, we tried to identify the factors which may increase or decrease, in a significant way, the odds that the decision-making process relates to a precise domain (pedagogic, scientific, institutional management or academic personnel), and that this process follows the characteristics of four decision-making models in current use: collegial, political, bureaucratic or anarchical model.